NODAL MEANINGS IN (B) BASMALA (IN THE NAME OF ALLAH THE MERCIFUL) - Mirza Mohammed, Yaseen (Journal of Duhok University, 2019)
In my point of view, an issue of a high importance in the interpretation (tafseer) of the Koran is the issue of the doctrinal aspects that should be taken into consideration before the other aspects when interpreting the holy Koran. I followed the methodology of traceability and extrapolation in the doctrinal, monotheistic books and interpretation (tafseer) books, then I extracted and collected scattered issues, compared and managed them with the right opinion, and (God knows all), it became a model for the interpretation of the nodal Koran, I have encountered difficulties that is related to the doctrine in which getting into it requires caution, careful accuracy and long researching that includes not attributing words and conversations to sources and references, the citation of weak conversations, words, linguistic views and frail. All that made me weary and took too much of my time. The results that I have reached are multiple opinions and differences that led to contradictions that should not exist or lead to that level of matter by the existence of a consensus opinion, especially it has been reported from the Prophet (may peace be upon him), when he gave the combination of speech including that the Koran is like a sea in its meanings and its’ purposes still need to be served in spite of all that has been offered before. I am content with that, and God is behind the intention.